Creating an Inclusive Society: The Role of Ethnic Social Movements in Promoting Equality and Inclusion in Ghana - Morgan, Anthony Kwame; Rahinatu, Ibrahim; Awafo, Beatrice Aberinpoka (Ethiopian Journal of Social Sciences, 2021)
Social movements are known to be great advocates of inclusivity. With the worldâ€™s considerable commitment to promoting social inclusion as contained in the Sustainable Development Goals (SDGs), the importance of social movements has been reinvigorated. Absent in the literature, however, is student minority ethnic movementsâ€™ role in promoting social inclusion in Ghana. This qualitative study provides an exploratory assessment of the roles of functional student minority ethnic groups in promoting equality among students of Kwame Nkrumah University of Science and Technology, from the perspective of movement members and their patrons. By relying on the qualitative-exploratory research design, in-depth interviews were conducted with 8 participants [comprising of members (3), executives (3) and patrons (2)] of three selected functional student minority ethnic groups (National Association of Nzema Students [NANS], Volta Region Studentsâ€™ Association [VORSA] and Dagomba Students Association [DASA]) in Kwame Nkrumah University of Science and Technology between April 24, 2020 and May 7, 2020. Data were thematically analysed and normative standpoints of participants were presented as quotations. The main findings were that the groups were formed to engender development and promote inclusion in varied forms across the different ethnic groups they represent. They have accomplished these through promoting gender, income, ethnic and spatial dimensions of inclusion by undertaking an array of activities. The ethnic social movements hold prospects for the development and promotion of inclusivity and equality. Nonetheless, these groups are confronted with issues of member apathy and financial constraints, thus hindering their efforts in implementing their programmes and activities. In tandem with the framing theory, leaders of the movements have a task to present or â€œframeâ€ the core values held by people it seeks to recruit by branding the movements in a way that appeals to them and fulfils their deeply held values.